Indications for particle precipitation impact on the ion-neutral collision frequency analyzed with EISCAT measurements - F. Günzkofer; G. Stober; G. Stober; J. Kero; D. R. Themens; D. R. Themens; A. Tjulin; N. Gulbrandsen; M. Tsutsumi; M. Tsutsumi; C. Borries (Annales Geophysicae)
The ion-neutral collision frequency is a key parameter for the coupling of the neutral atmosphere and the ionosphere. Especially in the mesosphere lower–thermosphere (MLT), the collision frequency is crucial for multiple processes, e.g., Joule heating, neutral dynamo effects, and momentum transfer due to ion drag. Few approaches exist to directly infer ion-neutral collision frequency measurements in that altitude range. We apply the recently demonstrated difference spectrum fitting method to obtain the ion-neutral collision frequency from dual-frequency measurements with the EISCAT incoherent scatter radars in Tromsø. A 60 h long EISCAT campaign was conducted in December 2022. Strong variations of nighttime ionization rates were observed with electron densities at 95 km altitude varying from Ne,95∼109<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="55pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="1f689d138420c01e4f4fd995676761f6"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="angeo-43-331-2025-ie00001.svg" width="55pt" height="17pt" src="angeo-43-331-2025-ie00001.png"/></svg:svg> to 1011 m−3, which indicates varying levels of particle precipitation. A second EISCAT campaign was conducted on 16 May 2024, capturing a solar energetic particle (SEP) event, exhibiting constantly increased ionization due to particle precipitation in the lower E region: Ne,95≳5×1010<mspace width="0.125em" linebreak="nobreak"/><mtext>m</mtext>-3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="98pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="7e4cf4304d3939c77aaab2d6cc3f8e40"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="angeo-43-331-2025-ie00002.svg" width="98pt" height="17pt" src="angeo-43-331-2025-ie00002.png"/></svg:svg>. We demonstrate variations of the ion-neutral collision frequency profile that we interpret as neutral particle uplift due to particle precipitation heating. Assuming a rigid-sphere particle model, we derive neutral density profiles which indicate a significant variation of neutral gas density between about 90–110 km altitude that correlate with the estimated strength of particle precipitation. However, the change in ion-neutral collision frequencies cannot be conclusively linked to the particle precipitation impact, and alternative interpretations are discussed. We additionally test the sensitivity of the difference spectrum method to various a priori collision frequency profiles.